Desafios para a formação do leitor crítico: promovendo a compreensão leitora de discursos polêmicos por meio da produção de podcast - Santos, Joyce Kelly Alves dos (2021)
Discursive comprehension and argumentative reading are challenging points in the teaching-learning process, as they are essential elements for the effective mastery of the language that requires the use of specific reading procedures in situations of interaction with the other's discourse. Therefore, this research was designed to improve students' argumentative resources with respect to the development of reading comprehension and argumentative and critical reading around controversial speeches, so that students could identify how discursive positions were constructed and materialized in various genres. The research was carried out on three fronts: i. from the observation of the way in which a subject was put into question; ii. through the perspective of themes; iii. for building justifications in sustaining and reinforcing ideas. This work was based on the studies of Grácio (2010) and Amossy (2017), and the action research methodology is based on Tripp (2005), on the reflections of Lerner (2002) and on the didactic-pedagogical dynamics of Muenchen and Delizoicov (2012) apud Azevedo and Freitag (2020). To this end, a reading project, with activities based on active methodologies, promoting argumentative reading practices that facilitated the identification of the elements that supported the discursive positions, was developed with the students of the 9th grade of Elementary School, from Colégio Estadual Luiz Alves de Oliveira, in Lagarto, Sergipe. The activities produced by students, during remote classes due to the social distancing resulting from the Covid-19 pandemic, led to the composition of the product of this professional master’s degree in Letters: a didactic module to assist the pedagogical practice of teachers in the classroom, in order to promote learning through the interaction of ideas and experiences. In addition, the research included the production of a collection of podcast episodes, in the form of a discussion table, on controversial topics chosen by the students. The program “Is it time to controversy?” it was created so that students could reflect and discuss controversial issues in circulation in society, and still produce positions before them, favoring the improvement in terms of reading comprehension, the exercise of argumentative reading and social participation.